PROBABILISTIC HAZARD ASSESSMENT, USING ARIAS INTENSITY EQUATION, IN THE EASTERN PART OF THE GULF OF CORINTH (GREECE) - Zygouri, V. (Bulletin of the Geological Society of Greece, 2010)
Shallow earthquakes cause serious damage near the trace of faults. The growth of major cities in hazard prone areas and the public anxiety associated with risks in critical facilities has focused attention to those areas. The Gulf of Corinth constitutes an area prone to high seismicity. During the last 2000 years several strong seismic events have caused extensive collapses, death casualties and widespread landslide phenomena. Strong motion attenuation relationships are considered a significant parameter for any earthquake hazard analysis. Attenuation relationships used in probabilistic hazard assessments predict ground motions components (in this case arias intensity) as a function of source parameters (magnitude and mechanism), propagation path (fault distance) and site effects (site class). In the eastern part of the Gulf of Corinth arias intensity equations were applied for a number of large E-W trending faults dominating the seismic potential of the area. Those faults have already been associated with landslide phenomena according to historic records and by using new methodologies a probabilistic approach of their behaviour has been accomplished for different recurrence intervals.